Combination Tests in the Diagnosis of Chronic Periprosthetic Joint Infection: Systematic Review and Development of a Stepwise Clinical Decision-Making Tool. (4th November 2020) - Abdelbary, Hesham; Cheng, Wei; Ahmadzai, Nadera; Carli, Alberto V.; Shea, Beverley J.; Hutton, Brian; Fergusson, Dean A.; Beaulé, Paul E.
Abstract : Background: Our objective was to identify combination tests used to diagnose chronic periprosthetic joint infection (PJI) and develop a stepwise decision-making tool to facilitate diagnosis. Methods: We conducted a systematic review of existing combinations of serum, synovial, and tissue-based tests for diagnosing chronic PJI after hip or knee replacement. This work is an extension of our systematic review of single tests, from which we chose eligible studies that also described the diagnostic performance of combination tests. Results: Thirty-seven eligible articles described the performance of 56 combination tests, of which 8 combinations had at least 2 studies informing both sensitivity and specificity. We also identified 5 types of combination tests: (1) a type-I Boolean combination, which uses Boolean logic (AND, OR) and usually increases specificity at the cost of sensitivity; (2) a type-II Boolean combination, which usually increases sensitivity at the cost of specificity; (3) a triage-conditional rule, in which the value of 1 test serves to triage the use of another test; (4) an arithmetic operation on the values of 2 tests; and (5) a model-based prediction rule based on a fitted model applied to biomarker values. Conclusions: Clinicians can initiate their diagnostic process with a type-II Boolean combination of serum C-reactive protein (CRP) and interleukin-6 (IL-6). False negatives of the combination can be minimized when the threshold is chosen to reach 90% to 95% sensitivity for each test. Once a joint infection is suspected on the basis of serum testing, joint aspiration should be performed. If joint aspiration yields a wet tap, a leukocyte esterase (LER) strip is highly recommended for point-of-care testing, with a reading of ++ or greater indicating PJI; a reading below ++ should be followed by one of the laboratory-based synovial tests. If joint aspiration yields a dry tap, clinicians should rely on preoperative tissue culture and histological analysis for diagnosis. Combinations based on triage-conditional, arithmetic, and model-based prediction rules require further research. Level of Evidence: Diagnostic Level III . See Instructions for Authors for a complete description of levels of evidence.